Preventive Detention of Children: A Case for Reform - Aminuddin, Mustaffa; Mohd Badrol, Awang; Nazli, Ismail@Nawang (2019)
Preventive detention refers to incarceration of an individual who has not yet been convicted, to prevent him from causing harm or endangering the community in some unspecified way. It is liberty deprivation of an individual based on the accusation of dangerousness. The issue of preventive detention on children has been regarded as one of the most controversial areas of juvenile justice policy which attracts debate from various legal scholars. In Malaysia, provisions of specific statutes that aim to prevent terrorism or national security have been invoked to justify preventive detention of children. The practice and application of these statutes on children have become a matter of great concern